Pengaruh Pembiayaan Murabahah Terhadap Pertumbuhan Usaha Mikro Anggota Bmt Maslahah Kc Panggungrejo Kota Pasuruan: Analisis Regresi Sederhana Menggunakan Software Jasp - Muchammad Toha (Universitas 45 Surabaya, 2025)
The purpose of this study is to analyze the effect of murabahah financing on the growth of micro-enterprises within the BMT Maslahah branch of Panggungrejo, Pasuruan City, as measured by asset and turnover indicators. This research is based on the important role of Islamic microfinance institutions in providing capital to small businesses amidst the limitations of conventional financial institutions. The method used is a quantitative approach with a simple linear regression model using JASP software. Primary data were collected through questionnaires distributed to 72 murabahah financing recipients, and secondary data were obtained from BMT internal reports. The results indicate that murabahah financing has a positive and significant effect on micro-enterprise growth, with a regression coefficient of 0.983 and a significance level of p <0.001. The coefficient of determination (R²) of 0.645 indicates that 64.5% of the variation in business growth can be explained by murabahah financing. These findings demonstrate that murabahah functions not only as a funding tool but also as a way to stimulate the economy based on Islamic principles.